MicroRNA-132 enhances transition from inflammation to proliferation during wound healing - Dongqing Li; Aoxue Wang; Xi Liu; Florian Meisgen; Jacob Grünler; Ileana R. Botusan; Sampath Narayanan; Erdem Erikci; Xi Li; Lennart Blomqvist; Lei Du; Andor Pivarcsi; et al. (The Journal of Clinical Investigation, 2015)
Wound healing is a complex process that is characterized by an initial inflammatory phase followed by a proliferative phase. This transition is a critical regulatory point; however, the factors that mediate this process are not fully understood. Here, we evaluated microRNAs (miRs) in skin wound healing and characterized the dynamic change of the miRNome in human skin wounds. miR-132 was highly upregulated during the inflammatory phase of wound repair, predominantly expressed in epidermal keratinocytes, and peaked in the subsequent proliferative phase. TGF-β1 and TGF-β2 induced miR-132 expression in keratinocytes, and transcriptome analysis of these cells revealed that miR-132 regulates a large number of immune response– and cell cycle–related genes. In keratinocytes, miR-132 decreased the production of chemokines and the capability to attract leukocytes by suppressing the NF-κB pathway. Conversely, miR-132 increased activity of the STAT3 and ERK pathways, thereby promoting keratinocyte growth. Silencing of the miR-132 target heparin-binding EGF-like growth factor (HB-EGF) phenocopied miR-132 overexpression in keratinocytes. Using mouse and human ex vivo wound models, we found that miR-132 blockade delayed healing, which was accompanied by severe inflammation and deficient keratinocyte proliferation. Together, our results indicate that miR-132 is a critical regulator of skin wound healing that facilitates the transition from the inflammatory to the proliferative phase.